2013
DOI: 10.1682/jrrd.2012.04.0067
|View full text |Cite
|
Sign up to set email alerts
|

Cycling exercise to resist electrically stimulated antagonist increases oxygen uptake in males: Pilot study

Abstract: Abstract-A hybrid training system (HTS) has been developed as the combined application of electrical stimulation (ES) and volitional contractions (VC), using electrically stimulated eccentric antagonist muscle contractions as a resistance to voluntary agonist muscle contractions. The purpose of the present study is to compare the metabolic cost between cycling exercise using HTS as added resistance (HTC) and unloaded cycling exercise (ULC). Twelve male subjects exercised on a leg cycle ergometer. After 5 min r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
3
13
0
Order By: Relevance
“…Indeed, there is still a certain consensus according to which VOL + ES would be not more efficient than VOL (with or without additional weight/load) or ES alone in order to improve motor and/or sport performance in chronic application whether with isometric, dynamic or plyometric movements (Paillard et al, 2005 ; Herrero et al, 2010 ; Park et al, 2016 ; Wirtz et al, 2016 ; Gomes da Silva et al, 2018 ). Yet, some recent papers showed that VOL + ES could bring some advantages in comparison with VOL and ES practiced alone as part of training programs aiming at improving motor performance in healthy subjects (Wahl et al, 2012 , 2014 , 2015 ; Matsuse et al, 2013 ; Mathes et al, 2017 ). Hence, it seems relevant to analyze why some studies reported benefit effects of VOL + ES in chronic application in comparison with VOL and ES in healthy subjects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there is still a certain consensus according to which VOL + ES would be not more efficient than VOL (with or without additional weight/load) or ES alone in order to improve motor and/or sport performance in chronic application whether with isometric, dynamic or plyometric movements (Paillard et al, 2005 ; Herrero et al, 2010 ; Park et al, 2016 ; Wirtz et al, 2016 ; Gomes da Silva et al, 2018 ). Yet, some recent papers showed that VOL + ES could bring some advantages in comparison with VOL and ES practiced alone as part of training programs aiming at improving motor performance in healthy subjects (Wahl et al, 2012 , 2014 , 2015 ; Matsuse et al, 2013 ; Mathes et al, 2017 ). Hence, it seems relevant to analyze why some studies reported benefit effects of VOL + ES in chronic application in comparison with VOL and ES in healthy subjects.…”
mentioning
confidence: 99%
“…From a metabolic viewpoint, some studies showed that acute metabolic changes (e.g., some respiratory, cardiac, biological and biochemical blood parameters) induced by exercise as well as energetic and mechanical output are greater during cycling with superimposed ES than during cycling alone (Wahl et al, 2012 , 2014 , 2015 ; Matsuse et al, 2013 ; Mathes et al, 2017 ). Hence, one can infer that ES during cycling exercise might be an enhancing stimulus for skeletal muscle metabolism and induced adaptations.…”
mentioning
confidence: 99%
“…A future HTS experiment of the lower extremity should be performed in weightlessness to prove its actual orbital effectiveness as mentioned above. HTS can be used with other exercise or training, and we tested it with an ergometer [ 21 ]. HTS was able to be used easily with the ergometer and functioned well.…”
Section: Discussionmentioning
confidence: 99%
“…During HTS training, both flexion and extension muscles contract simultaneously, and longitudinal force load will be applied on the sandwiched bone by these contracting muscles. Multiple ground-based experiments [ 16 21 ] and a parabolic flight verification [ 22 ] have been encouraging as to the possibility of use by astronauts, but, thus far, evaluation in space has not been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major advantages of HTS is that electrical stimulation can be combined with voluntary activity simultaneously. We have shown that HTS could be combined with aerobic cycling exercise simultaneously 26,27) . Walking is one of the most basic moderate intensity physical activities for elderly people.…”
Section: Introductionmentioning
confidence: 99%